A Study on the Representation of Women in Western Artworks from a Feminist Perspective - Zhao, Yundi (GBP Proceedings Series, 2025)
This study examines Western artworks through the lens of feminism, aiming to uncover and critically analyze the depiction and status of women in art, along with their profound socio-cultural implications. From the mythological goddesses of ancient Greece and Rome to the humanistic portrayals of women in the Renaissance, the courtly beauties of the Baroque and Rococo periods, and the realist and impressionist representations from the 19th to early 20th century, these evolving images not only reflect shifting societal perceptions of women's roles but also encapsulate transformations in power structures and gender dynamics. The development of feminist theory and art criticism has further enriched this field, providing deeper insights into the ways women have been marginalized and objectified in art. Moreover, it highlights how female artists have actively challenged traditional narratives through their own creative expressions. Feminist art criticism extends beyond the analysis of women’s representation in artworks, offering a critical examination of the underlying gender power relations and socio-cultural contexts. By reinterpreting Western art from this perspective, this research contributes to a broader discourse on gender equity, reinforcing the role of art as both a reflection of and a catalyst for social change.